Liberalização da conta de capitais e inflação: a experiência brasileira no período pós-real - Mendonça, Helder Ferreira de; Pires, Manoel Carlos de Castro (Estudos Econômicos (São Paulo), 2006)
In the 1990s the idea that capital account liberalization represented a mechanism for disciplining the conduction of the monetary policy in the search for price stability was developed. Based on this argument, a new version of Gruben e McLeod's (2001) model applying a dynamic public debt constraint to the monetary authority's utility function is made. Furthermore, an empirical analysis (through application of VAR) was made for the Brazilian case with the objective of evaluating if the increase in the capital account liberalization after the introduction of the Real Plan contributed to price stability. The findings denote that a decrease in the capital account liberalization is capable of attenuating inflationary pressure and that the duration of this effect depends on the exchange regime used.